IMPROVING THE STUDENTS’ VOCABULARY MASTERY BY USING STORYTELLING AT THE ELEVENTH GRADE OF LANGUAGE CLASS IN MAN MODEL 1 MANADO - Ahmad Mustamir Waris; Nikmala Nemin Kaharuddin; Fadhlan Saini; Fadila Lamante (Universitas Muhammadiyah Gorontalo, 2021)
The research aimed to find out the improvement of students’ vocabulary mastery by using storytelling. This research was conducted by using classroom action research (CAR). The subject of this research were the eleventh grade of language class in MAN Model 1 Manado which consisted of 16 students with 11 girls and 5 boys. This research conducted in two cycle, by each consisted of planning, acting, observing, and reflecting. Every cycle conducted in two meetings. The data were gathered through qualitative and quantitative data. The qualitative data were gained by observation and documentation. Then, quantitative data were obtained from the students vocabulary score of pre-test and post-test. Based on the result, it showed that there was a development of the students vocabulary mastery. It can be seen from the mean score of pre-test which was 60.9, while the mean score of post-test cycle one was 66.5 and the mean score of post-test cycle two was 84,3. In addiction there was one student (6,25%) who passed the minimum mastery criterion in the pre-test. Meanwhile, in the cycle one there were 2 students (12,5%) who passed the minimum mastery criterion (KKM) and it increased in the post-test cycle two that there were 15 students (93,7%) who passed the minimum mastery (KKM). Hence, the criteria of success were achieved. Furthermore, the result of observation showed that the students were motivated in the teaching learning process during the implementation of storytelling. Key words : Improving vocabulary mastery, storytelling